Copper oxide–reinforced ethyl vinyl acetate/ chlorinated polyethylene blend nanocomposites: eco-friendly design of high-performance electroactive materials - Shini, M.; Ramesan, M. T. (Frontiers in Materials, 2025)
Blend nanocomposites based on ethyl vinyl acetate (EVA) and chlorinated polyethylene (CPE), reinforced with different quantities of copper oxide (CuO) nanoparticles, were fabricated by a simple and eco-friendly two-roll mill mixing technique. Successful incorporation of nanoparticles into the blend matrix was confirmed by the characteristic peaks of CuO in FTIR and XRD. UV-Visible spectroscopy showed maximum absorption, a high refractive index and a low bandgap energy for the EVA/CPE/5 wt% CuO nanocomposite. Field emission scanning electron microscopy (FE-SEM) and high-resolution transmission electron microscopy (HR-TEM) investigations demonstrated uniform surface morphology and well-dispersed CuO nanoparticles at this concentration. Thermogravimetric analysis (TGA) indicated improved thermal stability of the blend with the incorporation of CuO. Impedance analysis revealed that 5 wt% CuO nanocomposites achieved the most significant enhancement in AC conductivity (from 2.8 × 10−7 S/cm to 1.17 × 10−6 S/cm at 1 MHz) and dielectric constant (43.39–156.87 at 100 Hz), accompanied by a reduction in activation energy. The electric modulus plots showed non-Debye relaxation behaviour, while the Nyquist plot showed the smallest semicircle, confirming its lowest impedance at this composition. Mechanical tests demonstrated that the 7 wt% CuO-loaded nanocomposites displayed the maximum tensile, tear, and impact strength, surpassing the pristine EVA/CPE blend by 60.8%, 113.5%, and 30.8%, respectively. These findings highlight the potential of EVA/CPE/CuO nanocomposites as next-generation electroactive materials for high-performance energy storage applications.